Study of effectiveness of bacteria isolated from rumen microbes with acetogen medium as methanogenesis inhibitor - Thalib, Amlius; Widiawati, Y; Hamid, H (Indonesian Animal Sciences Society, 2004)
Ruminal methanogenesis has disadvantageous effects on ruminant animals and environment of atmosphere. Inhibition of methane produced through reduction of carbondioxide has been conducted by bacteriological approach. The approach involved the isolation of bacteria from rumens of sheep (IBD) and buffalo (IBK) using medium for CO-utilizing acetogens. The isolate of bacterium was multiplied with the usual culture medium and then used as inoculum to degrade a substrate of King grass under constant temperature (390C) for 48 hours. Fresh rumen fluid of sheep (CRDS) was used as comparing inoculum. Measurementswere carbondioxide and methane gasses, pH, volatile fatty acid (VFA) and NH3-N contents, bacterial count, and dry matter digestibility (in vitro DMD). The data measured were analyzed by using completely randomized design. The results showed that morphological cell of IBD was oval pleomorphic with Gram negative type, and cell of IBK was rod with Gram negative type. Percentage of CH4 produced by inoculum of IBD was lower than CRDS but was not significantly different (29.47 vs. 33.07%), while the percentage of methane produced by inoculum of IBK was very significantly lower than CRDS (24.29 vs. 33.07%) (P<0.01). Acetate/propionate ratio as a result of substrate fermentation by inoculum of IBD (3.55) and IBK (3.79) were very significantly higher than that of CRDS (2.43) (P<0.01). It is concluded from this experiment that isolates used were effective to inhibit the methanogenesis and the species contained in the isolates were indicated to be homoacetogenic bacteria. Â Key words: Bacterial isolate, acetogen medium, methanogenesis, inhibitor